Breaking Social Norms: Lived Stories of The Unmarried Elderly - Boston, Jake; Garcia, Khristine Joy Barbosa (Universitas Ahmad Dahlan, 2024)
This study was conducted to uncover the lives of the unmarried elderly in the Southern Mindanao by providing useful information about their psychological well-being in terms of their positive thoughts, positive feelings, triumphs or successes, hopes or aspirations, and meaningful reasons for defying social norms. The study has ten (10) informants, composed of five unmarried men and five unmarried women carefully selected based on their predefined characteristics. In conducting the study, the researcher utilized a semi-structured interview guide questionnaire that was validated by three experts. The data were gathered through an in-depth interview with each of the informants, observations, and conversations with some key informants. All pertinent data were obtained using an electronic audio recorder and observational field notes. Consequently, all relevant data were transcribed, reviewed, and analyzed extensively through a thorough coding process and triangulation methods to come up with valid and reliable results. The results were discussed through a thematic analysis matrix to represent the data in an organized and comprehensive manner. After carefully examining the gathered data, this phenomenological inquiry has found significant findings. Particularly, their positive thoughts revealed three major themes, including individual functioning, social functioning, and a secured social network. Their positive feelings identified only one central theme, which is self-actualization. Only one main theme has emerged for their triumphs or successes, namely, their life accomplishments. For their hopes or aspirations, it also came up with one key theme: quality of life. Lastly, their meaningful reasons for breaking social norms have identified two significant themes: predetermination and self-determination. As indicated in the results of the study, the informants' positive attitudes across all aspects of their lives helped them understand their purpose or life's meaning. Thus, their optimistic view of life enabled them to function positively, which contributed significantly to their psychological well-being.